REVITALIZATION OF WATER RESOURCES LAW ENFORCEMENT: THE ROLE OF LOCAL WISDOM AND PARTICIPATION OF KOTABARU INDIGENOUS COMMUNITIES IN LEGAL ETHNOGRAPHY - Trisna Agus Brata; Abdul Halim Barkatullah; Imam Syafa’i (RADJA PUBLIKA, 2025)
Indonesia is facing a water resources (SDA) management crisis marked by a moderate Water Quality Index (IKA) and 112 drought-prone areas, exacerbated by environmental degradation and ineffective law enforcement of Law No. 17/2019 concerning Water Resources, 70% of cases are only resolved administratively). This study aims to identify the principles of Huma Betang in water law enforcement in Kotabaru, analyze the effectiveness of indigenous communities as law enforcement agents, and develop an ethnography-based adaptive revitalization model. The method uses a legal ethnography approach with in-depth interviews, participatory observation, and legal document analysis, analyzed thematically with triangulation. The findings show that the principles of Huma Betang (Ulayat Water Rights, Gawi Manuntung Waja, Belom Bahadat) reduce minor violations and resolve water disputes at the customary level, although they are hampered by integration with state law. The